Northernmost record of a poorly known tuskfish, Choerodon margaritiferus (Perciformes: Labridae), from southern Japan, and first description of a female - Miyamoto, Kei; Nonaka, Ai; Oka, Shin-Ichiro (Zootaxa, 2015)
We describe 5 specimens of Choerodon margaritiferus Fowler and Bean, 1928 (94.5–107.0 mm standard length, 1 male and 4 females) collected near Okinawa Island, southern Japan. This is the northernmost record of this species and the first record of it in Japanese waters; until now, C. margaritiferus was recorded only from the western central Pacific. This species was originally described on the basis of 1 male specimen, and all additional specimens described in the literature were also male. Morphological characters of both sexes are described, and new diagnostic characters of the female are presented.